2022
DOI: 10.1111/plb.13445
|View full text |Cite
|
Sign up to set email alerts
|

Soil VOC emissions of a Mediterranean woodland are sensitive to shrub invasion

Abstract: Many belowground processes, such as soil respiration and soil-atmosphere VOC (volatile organic compounds) exchange, are closely linked to soil microbiological processes. However, little is known about how changes in plant species cover, i.e. after plant invasion, alter these soil processes. In particular, the response of soil VOC emissions to plant invasion is not well understood.• We analysed soil VOC emissions and soil respiration of a Mediterranean cork oak (Quercus suber) ecosystem, comparing soil VOC emis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…After the second rain event C 3 H 8 OS soil fluxes recovered to pre-drought levels. Soil emissions of C 4 H 10 S, tentatively identified as isopropyl methyl sulfide, have been previously reported but its origin is not well understood 38 , 39 . Mancuso et al, 38 suggested C 4 H 10 S as a potential intermediate product of the dimethyl sulfide metabolic pathway.…”
Section: Resultsmentioning
confidence: 99%
“…After the second rain event C 3 H 8 OS soil fluxes recovered to pre-drought levels. Soil emissions of C 4 H 10 S, tentatively identified as isopropyl methyl sulfide, have been previously reported but its origin is not well understood 38 , 39 . Mancuso et al, 38 suggested C 4 H 10 S as a potential intermediate product of the dimethyl sulfide metabolic pathway.…”
Section: Resultsmentioning
confidence: 99%
“…The plethora of detected VOCs from soil collected from the selected flowerbeds suggested the presence of a complex substrate, i.e. , urban soils, where belowground processes, such as microbial respiration and exchange of VOCs, occurred [ 51 ]. However, and unexpectedly, it has been recently demonstrated that the amounts of various VOCs released from soils rose while the amount of microbial diversity in the soil decreased [ 52 ].…”
Section: Discussionmentioning
confidence: 99%